2023
DOI: 10.1093/molbev/msad025
|View full text |Cite
|
Sign up to set email alerts
|

Independent Innexin Radiation Shaped Signaling in Ctenophores

Abstract: Innexins facilitate cell-cell communication by forming gap junctions or non-junctional hemichannels, which play important roles in metabolic, chemical, ionic, and electrical coupling. The lack of knowledge regarding the evolution and role of these channels in ctenophores (comb jellies), the likely sister group to the rest of animals, represents a substantial gap in our understanding of the evolution of intercellular communication in animals. Here we identify and phylogenetically characterize the complete set o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Whereas gap junctions could be identified within the comb plates, as previously reported ( 15 ) in our SBFSEM data as well as in TEM micrographs, we found no evidence of similar structures between neurites of nerve-net neurons that would suggest the presence of electrical synapses. Additionally, a recent characterization of the complete set of M. leidyi innexins—responsible for the formation of gap junctions in invertebrates—did not show any mRNA expression in in situ hybridization experiments in nerve-net cell bodies ( 23 ). However, we did observe synaptic triads and plasma membrane contacts of unknown molecular structure that connect the SNN externally to polster and mesogleal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas gap junctions could be identified within the comb plates, as previously reported ( 15 ) in our SBFSEM data as well as in TEM micrographs, we found no evidence of similar structures between neurites of nerve-net neurons that would suggest the presence of electrical synapses. Additionally, a recent characterization of the complete set of M. leidyi innexins—responsible for the formation of gap junctions in invertebrates—did not show any mRNA expression in in situ hybridization experiments in nerve-net cell bodies ( 23 ). However, we did observe synaptic triads and plasma membrane contacts of unknown molecular structure that connect the SNN externally to polster and mesogleal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…As a wider range of modern techniques has recently become available in ctenophores (e.g., single‐cell RNAseq [Sebé‐Pedrós et al, 2018] and connectomics [Burkhardt et al, 2023]) and ctenophore species have progressed towards becoming established lab models (e.g., culturing and CRISPR/Cas9 knock‐outs have been reported [Presnell et al, 2022; Soto‐Àngel et al, 2022]), new critical insights into the biology of their neurons have been revealed. Earlier studies have established such key approaches as electrophysiology and calcium imaging in ctenophores; however, it has been achieved only in comb plates (Moss & Tamm, 1987; Tamm & Terasaki, 1994) and muscles (Moroz et al, 2014; Ortiz et al, 2023), while direct measurements of neuronal activity have not been reported. Thus, more experimental approaches are urgently required to understand the function of ctenophore neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We performed differential gene expression analyses on the B. ovata transcriptomic data we generated and on previously published transcriptomic data collected from the comb rows ( 35 ) and the aboral organs ( 76 ) of adult M. leidyi . These comparisons were used to investigate tissue-defining genes shared by the last common ancestor of B. ovata and M. leidyi .…”
Section: Methodsmentioning
confidence: 99%